Modelos de toxicidade da cisplatina em ratos adolescentes: papel protetor do disseleneto de difenila e do ebselen e avaliação da co-exposição ao estresse - Fulco, Bruna da Cruz Weber (2022)
Cisplatin is a recommended chemotherapy drug for the treatment of pediatric and adult neoplasms that, despite its wide use, is related to numerous serious adverse effects such as neurotoxicity. In animal models using adult rodents, cisplatin induces shortterm central peripheral toxic effects. Cisplatin-related toxicity mechanisms generally involve redox dysregulation and modulation of pathways associated with apoptosis. Going through a chronic illness and its treatment during childhood can be a stressful experience. Thus, the objective of this thesis was to standardize experimental models of short-term peripheral toxicity (nephrotoxicity and hepatotoxicity) and long-term central toxicity (anxious phenotype) in animals that received cisplatin in the adolescence period. The protective role of ebselen and diphenyl diselenide in peripheral toxicity and the impact of stress exposure on central toxicity were evaluated. Article 1 showed the nephrotoxic potential of a single administration of cisplatin 6mg/kg in juvenile rats, evidenced by the elevation of blood markers of renal damage in the tissue and disturbance of redox balance. Furthermore, the compounds ebselen and diphenyl diselenide were effective as nephroprotectors, due to their potential as modulating antioxidants of the Nrf2/Keap1/HO-1 pathway. In article 2, the same model also showed the hepatotoxic effects of cisplatin in juvenile animals, with the elevation of transaminases and lipemic markers. Oxidative damage and dysregulation of enzymes related to carbohydrate metabolism have also been shown in liver tissue. Ebselen and diselenide were efficient in protecting the animals from the changes caused by cisplatin, restoring both the redox balance and regulating carbohydrate metabolism. In manuscript 1, a stress model was established, based on the single prolonged stress (SPS) model, replacing the use of ether with social instability. The results show that the substitution of a chemical stressor for a social one was efficient in producing behavioral (anxious phenotype and cognitive impairment) and molecular (markers of physiological reactivity and decrease in proteins related to synaptic integrity) changes similar to those induced by the standard SPS, in addition to highlighting this animal model as a possible tool for the study of post-traumatic stress disorder. In manuscript 2, this model was used to assess whether exposure to stress at different stages of development would interfere with the anxious-like phenotype of adult Wistar rats that received cisplatin during the period corresponding to early adolescence. The results showed that generally females exhibited the anxious-like phenotype more pronounced than males and in a related manner to the age at which the animals were exposed to stress. These responses are related to the joint modulation of the apoptotic and autophagic pathways. Thus, this thesis contributes mainly by presenting animal models for the study of toxicity caused by cisplatin in developing animals.